2009
DOI: 10.2134/jeq2008.0168
|View full text |Cite
|
Sign up to set email alerts
|

A Biosecure Composting System for Disposal of Cattle Carcasses and Manure Following Infectious Disease Outbreak

Abstract: During outbreaks of infectious animal diseases, composting may be an effective method of disposing of mortalities and potentially contaminated manure. Duplicate biosecure structures containing 16 cattle (Bos taurus) mortalities (343 kg average weight) were constructed with carcasses placed on a 40-cm straw layer and overlaid with 160 cm of feedlot manure. At a depth of 80 cm (P80), compost heated rapidly, exceeding 55 degrees C after 8 d and maintained temperatures of 55 to 65 degrees C for > 35 d. Temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 51 publications
7
93
1
Order By: Relevance
“…of the envelope material without producing significant amounts of leachate. These results contrast with early field studies by Xu et al (2009) in which cattle carcasses composted in plastic-wrapped piles using feedlot manure as the envelope material exhibited highly variable m.c. with some pooling of leachate.…”
Section: Moisture Contentcontrasting
confidence: 99%
“…of the envelope material without producing significant amounts of leachate. These results contrast with early field studies by Xu et al (2009) in which cattle carcasses composted in plastic-wrapped piles using feedlot manure as the envelope material exhibited highly variable m.c. with some pooling of leachate.…”
Section: Moisture Contentcontrasting
confidence: 99%
“…Temperatures at or near 55°C are considered optimal (31), and we observed that a temperature of 55°C was reached or exceeded only late in the active composting phase of the control compost and never for AS700 compost. In addition, temperature is temporally and spatially variable within compost (39), consistent with the observations that temperatures were lower at the top than at the center of the compost and that a rapid rise in temperature followed compost turning. Nevertheless, heterotrophic bacterial populations typically exceeded 10 8 CFU g Ϫ1 (dry weight) regardless of treatment (i.e., control versus AS700) or location (i.e., top versus center).…”
Section: Discussionsupporting
confidence: 82%
“…Effective composting relies on the action of complex microbial communities including the generation of metabolic heat and enzymatic decomposition processes. Salient benefits of manure composting include decreased water and bulk (Ϸ50 to 70% reduction in volume) (31), destruction of weed seeds (21) and pathogens (34,39), and stabilization of a Extracted DNA was subjected to Campylobacter genus-specific PCR. Each replicate compost pile was oriented east to west.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations